2016
DOI: 10.1016/j.jgeb.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Seed coat color, weight and eye pattern inheritance in gamma-rays induced cowpea M2-mutant line

Abstract: Gamma radiation is a very effective tool for inducing genetic variation in characters of many plants. Black seeds of M2 mutant were obtained after exposure of an Egyptian cowpea cultivar (Kaha 1) to a low dose of gamma rays. Segregation of seed coat color, weight of 100 seeds and seed eye pattern of the black seeds of this mutant line were further examined in this study. Four colors were observed for seed coat in the M3 plants ranging from cream to reddish brown and three eye patterns were distinguished from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 30 publications
4
18
0
Order By: Relevance
“…Our results showed that, in general, the gene 562 diversity and the PIC were close (Fig 5), suggesting the evenness of allele's frequencies in the 563 mutant populations as reported by Shete values ranging from 0.25 to 0.5 and slightly informative at less than 0.25. Based on this, the 566 ISSR827, ISSR844, ISSRHB9, ISSR17899B and ISSR809 were moderately informative, the 567 remaining markers were slightly informative which were higher than the scores recorded in 568 the cowpea mutant population developed by Gaafar et al [12]. These differences could be 569 attributed to the low irradiation dose (50 Gy) used which might induce less mutations and less 570 variability compared to the 300 Gy and 340 Gy employed in this study.…”
Section: Genetic Diversity Induced By Mutagenesis Revealed By Issr Mamentioning
confidence: 60%
See 3 more Smart Citations
“…Our results showed that, in general, the gene 562 diversity and the PIC were close (Fig 5), suggesting the evenness of allele's frequencies in the 563 mutant populations as reported by Shete values ranging from 0.25 to 0.5 and slightly informative at less than 0.25. Based on this, the 566 ISSR827, ISSR844, ISSRHB9, ISSR17899B and ISSR809 were moderately informative, the 567 remaining markers were slightly informative which were higher than the scores recorded in 568 the cowpea mutant population developed by Gaafar et al [12]. These differences could be 569 attributed to the low irradiation dose (50 Gy) used which might induce less mutations and less 570 variability compared to the 300 Gy and 340 Gy employed in this study.…”
Section: Genetic Diversity Induced By Mutagenesis Revealed By Issr Mamentioning
confidence: 60%
“…These differences could be 569 attributed to the low irradiation dose (50 Gy) used which might induce less mutations and less 570 variability compared to the 300 Gy and 340 Gy employed in this study. In addition, Gaafar 571 and coworkers [12] used ethidium bromide for DNA staining which is less sensitive than 572…”
Section: Genetic Diversity Induced By Mutagenesis Revealed By Issr Mamentioning
confidence: 99%
See 2 more Smart Citations
“…These inter repeats are highly polymorphic in their sizes even among closely related genotypes as the result of the deficiency of evolutionary functional constraints in these functioning regions. Also, it is a technique that is widely used for assessing the alteration in DNA sequences induced by mutagenic agents such as gamma rays 5 . Additionally, ISSRs have been used successfully in genome mapping for a variety of crop species including maize, rice, barley and wheat 6,7 .…”
Section: Introductionmentioning
confidence: 99%